422 Developing foundational courses to support undergraduate student success in animal science departmental core curriculum. (5th December 2019) - Dunlap, Kathrin; Early, Lonisa; Fowler, Debra; Wickersham, Tryon
Abstract: Today's student population comes from highly diverse culture and socio-economic backgrounds, entering college with a range of life experiences and professional aspirations. The selection of and success upon entering a major is highly influenced by those factors. As society has progressed the principle purposes of the animal science discipline have remained intact but the industry scope has expanded as has the range of background knowledge and experience of students entering the major. To address these changes a data-driven, student-centered curriculum study was conducted. Amongst the study findings was that there exists a gap between existing student knowledge and skills, and faculty expectations upon entering disciplinary core courses, which were deemed necessary to gain proficiency in areas identified by industry stakeholders. In order to bridge this gap, it was a goal of the department to create foundational level courses that would support the department curriculum. Through the collaborative efforts between faculty within the animal science department and members of the university center for teaching excellence, as well as findings from the data generated as part of the curriculum redesign process, two new courses were identified for development: Farm Animal Biosystems and Livestock Production Systems. These courses illustrate a novel approach to addressing the disparity in student background knowledge and skills. Rather than assuming a level of proficiency with skills and addressing gaps in knowledge or vice versa, these key areas have been identified and separated so as to provide students with a solid foundation in both the scientific and applied components of the discipline, thus promoting success within the remainder of the curriculum. Successful completion of these courses will enable student to enter the specialized discipline core classes with a more uniform knowledge base.